ANALISIS AFIKSASI KARANGAN SISWA KELAS VI SD NEGERI 4 BERABAN, KEDIRI, TABANAN - Komang Ade Sarwidta; I Wayan Simpen; Ni Putu N. Widarsini (CV. ADIBA AISHA AMIRA, 2026)
This research aims to identify and analyze the use of affixation in the compositions written by sixth-grade students of SD Negeri 4 Beraban, Kediri, Tabanan. The most dominant types of affixation observed include prefixes, suffixes, circumfixes, and combined affixes. This research employs a qualitative descriptive approach. The data collection method used is the observational method (simak), with the basic technique of tapping (sadap), followed by advanced techniques, namely non-participatory observation (simak bebas libat cakap) and recording. The results of this study indicate that, in the students’ compositions, the most frequently occurring prefixes are me(N)-, di-, ter-, se-, and ber-. In addition, the most dominant suffix identified is -an. One circumfix that appears most frequently is ke-/-an. Lastly, the most commonly found combined affix is per-/-an. Several factors contribute to the occurrence of these types of affixation. These include the thematic focus of the compositions, which predominantly revolve around holidays; the fact that most of the compositions are narrative in nature; and the students’ prior exposure to affixation instruction from the fourth through the sixth grade. Based on these findings, it can be concluded that the students are capable of using affixes appropriately in terms of form, function, and meaning, as well as applying them effectively in their written compositions.